PENGARUH MODEL PEMBELAJARAN PROBLEM BASED INTRUCTION (PBI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA POKOK BAHASAN PERSAMAAN LINEAR SATU VARIABEL DI PONPES SALAPIAH GUNUNG SILAYANGLAYANG - Susi Sulastri Lubis; Nurdalilah Nurdalilah; Rayana Rayana (JURNAL MathEdu (Mathematic Education Journal), 2022)
The development of the era followed by technological developments also affects the learning paradigm, from conventional to modern. Technological innovation in education is increasingly sophisticated, so that subject matter can be mixed and delivered with technological advances. The current learning paradigm is more student-centered and the teacher occupies a position as a facilitator. The reality that occurs in the field shows that the courage of students to ask questions, express opinions, and students' curiosity in the learning process is still lacking. The purpose of this study was to determine the effect of the Project Based Instruction learning method on student learning outcomes. The research method used is classroom action research using two cycles carried out in the first semester with Number Pattern Material. The population in this study were students of class VII Ponpes Salapiah Gunung Silayang Layang. The results showed that there was a significant effect of student learning outcomes in learning mathematics through the Problem Based Instruction (PBI) learning model, which increased by 71.85 with the "Enough" category in the first cycle, then increased to 88.55 with the "Good" category in the first cycle. cycle II. The teacher's ability to manage learning using the Problem Based Instruction (PBI) model increased by 9.47%.